PENDAFTARAN TANAH SERTIPIKAT HAK MILIK TANAH YANG TUMPANG TINDIH DENGAN SERTIPIKAT HAK GUNA USAHA: Land Registration Certificate of Overlapping Land Ownership Rights with Cultivation Rights Certificate - Muhammad Rhifo Herfi Wijaya; Lisyowati Sumanto (AMICUS CURIAE, 2025)
Overlapping land title certificates often occur in the community, indicating that there is an administrative flaw in the making of the certificate, this happened in the case of Decision No. 36/G/2023/PTUN.BJM. The identification problems are as follows: 1) Is granting a Land Ownership Certificate on the Land Use Rights owned by PT? Sarana Subur Agrindotama by the Tanah Laut Regency Land Office by the provisions of the law? 2) What are the legal consequences of PT owning the Land Ownership Certificate on the Land Use Rights? Sarana Subur Agrindotama after the Banjarmasin PTUN Decision No. 36/G/2023/PTUN.BJM. This research is a normative legal research with a descriptive nature, the data used is secondary data obtained through literature studies and analyzed qualitatively by concluding deductively. The study results and conclusion indicate that a Land Ownership Certificate on the Land Use Rights owned by PT should be granted. Sarana Subur Agrindotama by the Tanah Laut District Land Office, there is a legal administrative flaw and the legal consequences for the Certificate of Ownership over the Land Use Rights owned by PT. Sarana Subur Agrindotama from the plaintiffs can be canceled.